Role of Maltose Enzymes in Glycogen Synthesis by Escherichia coli - Park, Jong-Tae (American Society for Microbiology, 2011)
Mutants with deletion mutations in the glg and mal gene clusters of Escherichia coli MC4100 were used to gain insight into glycogen and maltodextrin metabolism. Glycogen content, molecular mass, and branch chain distribution were analyzed in the wild type and in ΔmalP (encoding maltodextrin phosphorylase), ΔmalQ (encoding amylomaltase), ΔglgA (encoding glycogen synthase), and ΔglgA ΔmalP derivatives. The wild type showed increasing amounts of glycogen when grown on glucose, maltose, or maltodextrin. When strains were grown on maltose, the glycogen content was 20 times higher in the ΔmalP strain (0.97 mg/mg protein) than in the wild type (0.05 mg/mg protein). When strains were grown on glucose, the ΔmalP strain and the wild type had similar glycogen contents (0.04 mg/mg and 0.03 mg/mg protein, respectively). The ΔmalQ mutant did not grow on maltose but showed wild-type amounts of glycogen when grown on glucose, demonstrating the exclusive function of GlgA for glycogen synthesis in the absence of maltose metabolism. No glycogen was found in the ΔglgA and ΔglgA ΔmalP strains grown on glucose, but substantial amounts (0.18 and 1.0 mg/mg protein, respectively) were found when they were grown on maltodextrin. This demonstrates that the action of MalQ on maltose or maltodextrin can lead to the formation of glycogen and that MalP controls (inhibits) this pathway. In vitro, MalQ in the presence of GlgB (a branching enzyme) was able to form glycogen from maltose or linear maltodextrins. We propose a model of maltodextrin utilization for the formation of glycogen in the absence of glycogen synthase.